The hpCADD NDDO Hamiltonian: Parametrization - Thomas, Heike Bettina; Hennemann, Matthias; Kibies, Patrick; Hoffgaard, Franziska; Guessregen, Stefan; Hessler, Gerhard; Kast, Stefan M.; Clark, Timothy (Journal of Chemical Information and Modeling, 2017)
A neglect of diatomic differential overlap (NDDO) Hamiltonian has been parametrized as an electronic component of a polarizable force field. Coulomb and exchange potentials derived directly from the NDDO Hamiltonian in principle can be used with classical potentials; thus forming the basis for a new generation of efficiently applicable multipolar polarizable force fields. The new hpCADD Hamiltonian uses force-field-like atom types and reproduces the, electrostatic properties (dipole moment, molecular electrostatic potential) and Koopmans theorem ionization potentials closely, as demonstrated fora large training set and an independent test set of small molecules. The Hamiltonian is not intended to reproduce geometries or total energies. ell, as these will be controlled by the Classical force-field potentials. In order to establish the hpCADD Hamiltonian as an electronic component in force-field-based. calculations, we tested its performance in combination with the 3D reference interaction site model (3D RISM) for aqueous solutions. Comparison of the resulting solvation free energies for the training and test Sets to atomic charges derived from standard procedures, exact solute-solvent electrostatics-based on high-level quantum-chemical reference data, and established semiempirical Hamiltonians demonstrates the advantages of the hpCADD parametrization.